Fortifying the Frontline: The Critical Role of Endpoint Security in Cyber Defense - MS, Madhulika Badanpet (IPHO-Journal of Advance Research in Science And Engineering, 2026)
The rapid expansion of distributed computing, cloud services, and remote work has fundamentally transformed enterprise attack surfaces, placing endpoint devices at the center of modern cybersecurity risk. This article presents a comprehensive analytical framework for understanding endpoint security as a layered, adaptive defense system rather than a collection of isolated tools. Drawing upon empirical breach data, threat intelligence reports, and industry security architectures, this work examines the evolution of endpoint-centric attack vectors, the technological foundations of modern endpoint protection platforms, and the role of artificial intelligence in detecting and mitigating advanced threats. The paper further introduces a structured model for evaluating endpoint security maturity that integrates identity, device integrity, behavioral telemetry, and data protection. This research contributes to the cybersecurity field by providing a systematic, data-driven approach for aligning endpoint defense strategies with Zero Trust and enterprise risk management objectives.